Students Experiment of Online Classes during the Pandemic of COVID-19 and their Socio-economic affection toward Psychological impact on their Learning Behaviors’ (With Special Reference to University of Karachi) - Farooq, Dr. Kinza; Shah, Dr. Nasreen Aslam; Bashir, Dr. Siraj; Nadeemullah, Dr. Muhammad; Ali, Dr. Aliya (The journal of contemporary issues in business and government, 2022)
Millenary we are seeing the world changing for the second time. There was diversity before 9/11 and it changed the complete picture of demographical status, socio-economic condition, and social movement. There might be a global change again after COVID-19. In this pandemic where the people already suffering from socio-economic inequality, if we exaggerate the students‟ perspectives and they found that online learning couldn‟t produce desired results in underdeveloped countries like Pakistan, where most of the students are unable to access the internet due to technical as well as financial issues. Accordingly, the quick speed of COVID- 19 became a big challenge for the massive number of the students to get the lecture of courses offline in the classrooms. Moreover, due to the ripped spread of Covid-19 created an E-learning environment where the instruction of online network system to enhance the quality of teaching and learning to manage their provided contents accurately and managed their online classes and courses.The research objectives of the present papers contain with, to investigate the awareness of Covid-19 in university students, socioeconomic status of students, the problems faced by students in the pandemic, the curriculum satisfaction of students, the experience of online classes on students, and the lack of internet resources in students. While the hypotheses likewise (a) Students learning behavior affected by taking online classes. (b) By attending the online classes, student‟s study became disturbed in the Covid-19 pandemic. The present study was “Explanatory” in nature. The Universe was the University of Karachi. The researchers selected the mix-method likewise qualitative and quantitative strategy for data collection. The respondent has comprised the students of (First and Second Minor). The convenience sampling techniques adopted through which 65 respondents have been selected for the data collection, included three case studies. A tailor-made such as questionnaire and observations are used for data collection.